Influence of Package Visual Cues of Sweeteners on the Sensory-Emotional Profiles of Their Products - Wisdom Wardy (2018)
© 2017 Institute of Food Technologists® Substantial evidence suggests influence of color, physical state, and other extrinsic features on consumer perception and acceptability of food products. In this study, 560 subjects evaluated liking and emotional responses associated with 5 sweeteners (sucralose, stevia, saccharin, aspartame, and sucrose) under 2 eliciting conditions: control (brand name only) and informed (brand name/packet image), to assess impact of the packet color. For a given condition, 5 identical tea samples each labeled with a sweetener type were rated for sweetness and overall liking (9-point) and emotions (5-point). Nonsignificant interactions between eliciting condition and sweetener type were found for liking attributes and emotions (except peaceful), indicating their independent effects. However, overall differences existed among sweetener types and eliciting conditions based on both hedonic and emotional responses (MANOVA, P < 0.05), suggesting modulating effects of packet color on sweetener type in the sensory-emotion space. The sensory-emotion profile for sucrose was separate from that of nonnutritive sweeteners, with statistically significant Mahalanobis distances among sample centroids. Increases in positive emotion intensities contrasted with a decrease in negative emotion intensities were observed for some sweeteners moving from the control to informed condition. Sweetness liking was strongly correlated with the emotion satisfied (sucralose, saccharin) only in the control condition, whereas it was strongly correlated with the emotions pleas ed and satisfied (stevia), disgusted (aspartame), and satisfied (sucrose) only in the informed condition. Overall, results suggested that sensory liking and emotions during the consumption experience are related not entirely to the type of sweetener, but also the color of the packet.